Effect of kieselguhr on specific cake resistance in constant pressure filtration of pectin extract from orange peel - Kar, F; Arslan, N (Assn Food Scient Techn India, 1999)
Pectin extact was vacuum-filtered at 10, 15, 20 and 25 degrees C under various pressure differences (0.20 x 10(5) Pa. 0.33 x 10(5) Pa and 0.47 x 10(5) Pa) and the average specific cake resistances obtained. It was found that the cake obtained from constant pressure filtration of pectin extract from orange peel was compressible and the specific cake resistance was a function of applied pressure difference. A decrease was observed in specific cake resistance with increasing body feed concentrations. A further decrease of specific cake resistances was observed, when pre-coating and body feed were used together.
Keywords: orange peel; pectin; filtration; kieselguhr; specific cake resistance